As this sort of stone has hitherto met with few observers Basalt um 1800 - Haug, Henrike 1974- (2023)
This spotlight discusses the interrelation between a natural material (basalt) and a man-made artificial substance (black basalt ware). From 1769 onwards, the famous English ceramist Josiah Wedgwood produced his "black basalt ware". Firstly it refers to the black-figure Attic vases, among others shown in the Hamilton collection, and thus takes into account the enthusiasm for ancient greek culture of the time. The name of the ceramic mass, however, points to a second reference material – and thus relates it to the fashionable stone basalt, which is gaining great importance in the contemporary debate about the evolution of the Earth’s history.